Concussions in young adult athletes: No effect on cerebral white matter - Hoffman, Linda J.; Mis, Rachel E.; Brough, Caroline; Ramirez, Servio; Langford, Dianne; Giovannetti, Tania; Olson, Ingrid R. (Frontiers in Human Neuroscience, 2023)
The media’s recent focus on possible negative health outcomes following sports-related concussion has increased awareness as well as anxiety among parents and athletes. However, the literature on concussion outcomes is equivocal and limited by a variety of diagnostic approaches. The current study used a rigorous, open-source concussion identification method—the Ohio State University Traumatic Brain Injury Identification method (OSU TBI-ID) to identify concussion and periods of repeated, subclinical head trauma in 108 young adult athletes who also underwent a comprehensive protocol of cognitive tests, mood/anxiety questionnaires, and high-resolution diffusion-weighted brain imaging to evaluate potential changes in white matter microstructure. Results showed that athletes with a history of repetitive, subclinical impacts to the head performed slightly worse on a measure of inhibitory impulse control and had more anxiety compared to those who never sustained any type of head injury but were otherwise the same as athletes with no history of concussion. Importantly, there were no group differences in neural white matter as measured by tract-based spatial statistics (TBSS), nor were their any associations between OSU TBI-ID measures and whole-brain principal scalars and free-water corrected scalars. Our results provide support for the hypothesis that it is not concussion per se, but repetitive head impacts that beget worse outcomes.